Odorant Receptor PxylOR11 Mediates Repellency of Plutella xylostella to Aromatic Volatiles - Liu, Yipeng; Zhang, Sai; Liu, Yang; Wang, Guirong (Frontiers in Physiology, 2022)
Insects can use plant volatiles to guide certain behaviors, such as courtship, mating, host positioning, and habitat selection. Plutella xylostella is a global agricultural pest and has always been closely studied, but relatively few studies assess the molecular mechanism of P. xylostella exposed to plant volatiles. In this study, we analyzed the role of the odorant receptor PxylOR11 when P. xylostella is exposed to plant volatiles. Our analysis of tissue expression demonstrated that PxylOR11 is expressed in the antennae and that expression levels in female moths were significantly higher than in male moths. Functional analyses using the Xenopus oocyte expression system demonstrated that PxylOR11 was tuned to three aromatic compounds: benzyl alcohol, salicylaldehyde, and phenylacetaldehyde. Electroantennogram analyses revealed that these three aromatic compounds can induce electrophysiological responses in the antennae of P. xylostella, and that the EAG response value of female moths was significantly higher than that of male moths. Dual-choice bioassays demonstrated that the three aromatic compounds have a repellent effect on female P. xylostella. These results suggest that PxylOR11 has a role in mediating the repellent effect of aromatic volatiles on P. xylostella and can be used as a potential target to design novel olfactory regulators controlling P. xylostella.